Effects of Censoring Explicit Language in Music on Resistance Exercise Performance - Christopher G. Ballmann; Sophia L. Porrill; Rebecca R. Rogers; Zachary H. Ervin; Brittany R. Neal; Haley M. Nguyen; Phoebe N. Spears; Jonathan E. Strickland; Jesus Zavala; Nicholas B. Washmuth (Journal of Functional Morphology and Kinesiology, 2025)
Background: Listening to music has been widely reported to improve resistance exercise performance. However, few studies have considered lyrical content. The act of using explicit language has been shown to alter performance and psychophysiological responses to exercise. Although explicit language is widely used in mainstream music, it is unknown if altering explicit lyric content in music influences performance and psychophysiological responses to resistance exercise. Thus, the purpose of this study was to investigate the effects of censoring explicit lyrical music on bench press performance and psychophysiological responses to exercise. Methods: In a counterbalanced crossover manner, resistance-trained males (n = 11) were subjected to two conditions, namely (1) explicit music (EM) or (2) censored music (CM). Following a warm-up, music played continuously as participants completed 2 sets × 2 repetitions as explosively as possible, while a linear position transducer monitored the mean velocity of the barbell. Participants then completed 3 sets × repetitions to failure (RTFs) at 60% of a 1-repetition maximum (1-RM) separated by 2 min of rest. Motivation to exercise, psychological arousal, and rating of perceived exertion (RPE) were measured post-exercise. Total RTFs, mean velocity, motivation, psychological arousal, and RPE were compared between music conditions. Results: Findings show that total RTFs (p = 0.012) was significantly lower with CM versus EM, while mean velocity (p = 0.844) was not different between conditions. Psychological arousal (p = 0.005) and motivation (p = 0.002) were lower with CM versus EM. CM also resulted in a higher RPE (p = 0.011) compared to EM. Conclusions: Findings suggest that CM results in worse repetition volume compared to EM during resistance exercise but does not influence explosive ability. Changes in performance may be due to underlying decreases in motivation and psychological arousal. CM may also cause less dissociation, as evidenced by a higher RPE. Future research investigating the effects of lyrical content on exercise performance is warranted to further support current findings.